BEHIND CULTURAL LEGACY CONFLICT BETWEEN INDONESIA AND MALAYSIA - Moh. Nizar (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2017)
Based on results of research, the background of cultural legacy conflict (2007-2009) between Indonesia and Malaysia contained two aspects: economy and socio-political ones. Firstly, with respect to economy, Malaysia started to develop its economy through tourism industry based on cultural legacy. In this case, the diversity of Malaysia culture economically disregarded before, was expanded for tourism industry by performing cultural shows, festivals and exhibitions. As Indonesia society know these developments, it became heated, due to almost all of cultural legacies in archipelago societies inherited by Indonesia ancestors, were claimed by Malaysia. Indonesia local and central governments, therefore, countered it by advancing the patent rights of their cultural legacy without delay. Secondly, in terms of socio-politics, in addition to tourism promotion, tourism advertisements are aimed to get sympathy of Malay ethnic following national election in 2008 and retain dominance of United Malays National Organization (UMNO) in Malaysian government. As Malaysian government under Prime Minister Abdullah Badawi (2004-2008) faced dissatisfaction of Malaysia society to UMNO that gave opportunity to Anwar Ibrahim as opposition figure to engage the succeeding election, UMNO found out the political campaign based on tourism industry to maintain its power and blocked Anwar involvement in the election. At the same time, political vested interests exploited the bilateral dispute to shake the elected Susilo Bambang Yudhoyono as Indonesia President for 2009-2014. Political arena in Indonesia, then, became heated as mass media all together published the Indonesia cultural legacy claimed by Malaysia. It caused Indonesia society angrier due to it watched on Malaysia plundering its cultural identity, so that bilateral relationship.